Bark beetles and pinhole borers recently or newly introduced to France (Coleoptera: Curculionidae, Scolytinae and Platypodinae) - Barnouin, Thomas; Soldati, Fabien; Roques, Alain; Faccoli, Massimo; Kirkendall, Lawrence R.; Mouttet, Raphaëlle; Daubree, Jean-Baptiste; Noblecourt, Thierry (Zootaxa, 2020)
We present an annotated list of 11 Scolytinae and Platypodinae species newly or recently introduced to France. Four species are recorded for the first time as interceptions: Euplatypus hintzi (Schaufuss), Euplatypus parallelus (Fabricius), Xyleborus affinis Eichhoff and Xyleborus ferrugineus (Fabricius). Two are possibly naturalised: Xyleborus bispinatus Eichhoff and Cryphalus dilutus Eichhoff, while Cyclorhipidion distinguendum (Eggers) and Xyloterinus politus (Say) are confirmed as species newly established in Europe. Moreover, an unidentified species of Amasa Lea, collected previously in Spain, is recorded for the first time in France: Amasa sp. near truncata (Erichson). We point out that literature references to Amasa truncata as an invasive species in New Zealand and South America are incorrect, as the photographs of these non-native populations do not match the holotype of A. truncata. For each species we have updated its global distribution, detailed all French records, and summarized biology, ecology, host trees and potential risks as pests.